Running‐wheel activity delays mitochondrial respiratory flux decline in aging mouse muscle via a post‐transcriptional mechanism. Issue 1 (9th November 2017) - Stolle, Sarah; Ciapaite, Jolita; Reijne, Aaffien C.; Talarovicova, Alzbeta; Wolters, Justina C.; Aguirre‐Gamboa, Raúl; van der Vlies, Pieter; de Lange, Kim; Neerincx, Pieter B.; van der Vries, Gerben; Deelen, Patrick; Swertz, Morris A.; et al.
Summary: Loss of mitochondrial respiratory flux is a hallmark of skeletal muscle aging, contributing to a progressive decline of muscle strength. Endurance exercise alleviates the decrease in respiratory flux, both in humans and in rodents. Here, we dissect the underlying mechanism of mitochondrial flux decline by integrated analysis of the molecular network. Mice were given a lifelong ad libitum low‐fat or high‐fat sucrose diet and were further divided into sedentary and running‐wheel groups. At 6, 12, 18 and 24 months, muscle weight, triglyceride content and mitochondrial respiratory flux were analysed. Subsequently, transcriptome was measured by RNA‐Seq and proteome by targeted LC‐MS/MS analysis with 13 C‐labelled standards. In the sedentary groups, mitochondrial respiratory flux declined with age. Voluntary running protected the mitochondrial respiratory flux until 18 months of age. Beyond this time point, all groups converged. Regulation Analysis of flux, proteome and transcriptome showed that the decline of flux was equally regulated at the proteomic and at the metabolic level, while regulation at the transcriptional level was marginal. Proteomic regulation was most prominent at the beginning and at the end of the pathway, namely at the pyruvate dehydrogenase complex and at the synthesis and transport of ATP. Further proteomic regulation was scattered across the entire pathway, revealing an effective multisite regulation. Finally, reactions regulated at the protein level were highly overlapping between the four experimental groups, suggesting a common, post‐transcriptional mechanism of muscle aging.